A CNT (carbon nanotube) paper as cathode gas diffusion electrode for water management of passive μ-DMFC (micro-direct methanol fuel cell) with highly concentrated methanol. (15th March 2015) - Deng, Huichao; Zhang, Yufeng; Zheng, Xue; Li, Yang; Zhang, Xuelin; Liu, Xiaowei
Abstract: A novel MEA (membrane electrode assembly) structure of passive μ-DMFC (micro-direct methanol fuel cell) controls water management and decreases methanol crossover. The CNT (carbon nanotube) paper replacing CP (carbon paper) as GDL (gas diffusion paper) enhances water back diffusion which passively prevents flooding in the cathode and promotes low methanol crossover. Moreover, the unique structure of CNT paper can also enhance efficiency of oxygen mass transport and catalyst utilization. The passive μ-DMFC with CNT-MEA exhibits significantly higher performance than passive μ-DMFC with CP-MEA and can operate in high methanol concentration, showing the peak power density of 23.2 mW cm −2 . The energy efficiency and fuel utilization efficiency are obviously improved from 11.54% to 22.7% and 36.61%–49.34%, respectively, and the water transport coefficient is 0.47 which is lower than previously reported passive μ-DMFC with CP. Highlights: This novel GDL (gas diffusion layer) solves water management and methanol crossover. This GDL creates a hydraulic pressure in the cathode increasing water back diffusion. This GDL improves the electrical conductivity and activity of catalyst.